Out of This World : A Journey of Healing - Swander, Mary (Bur oak book., 2008)
When a life-threatening allergic illness demanded that she eat only organically grown food, writer and professor Mary Swander built a new life in a former one-room Iowa schoolhouse in the middle of the largest Amish community west of the Mississippi. In this rich and engaging memoir, which follows the course of a farmer’s year, she writes from the well-named Fairview School to share the radical transformation of her life.